2014
DOI: 10.1136/jech-2014-204708
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a brief primary care intervention to reduce passive smoking in babies: a cluster randomised clinical trial

Abstract: Clinical Trials.gov Identifier: NCT00788996.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Electronic and hand searching identified 550 records, with 493 references remaining after the removal of duplicates. Based on title and abstract screening, 103 relevant articles were retrieved for full-text assessment, with the final inclusion of 16 primary controlled trials [ 5 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ] (associated with 41 articles, Table S1 ). Twelve of these trials had previously been identified by Behbod and colleagues [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Electronic and hand searching identified 550 records, with 493 references remaining after the removal of duplicates. Based on title and abstract screening, 103 relevant articles were retrieved for full-text assessment, with the final inclusion of 16 primary controlled trials [ 5 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ] (associated with 41 articles, Table S1 ). Twelve of these trials had previously been identified by Behbod and colleagues [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Full trial characteristics are shown in Table S2 (including population, sample size, details of the intervention and control, outcome measures, and process indicators). Twelve trials [ 5 , 38 , 39 , 41 , 42 , 44 , 45 , 46 , 47 , 48 , 49 , 52 ] were randomised controlled trials (RCTs), three were cluster RCTs [ 40 , 50 , 51 ], and one was a non-randomised controlled trial [ 43 ]. Most trials were conducted in the USA [ 5 , 40 , 42 , 43 , 44 , 45 , 47 , 48 , 49 , 51 ], with the remaining trials in China [ 38 , 39 , 41 , 52 ], Germany [ 46 ], and Spain [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations